The effect of subsidies on R&D investment and success: do subsidy history and size matter? - Birgit Aschhoff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This study provides insights into the effects of public R&D grants on R&D input and output of firms from Germany. Previous research has shown that the allocation of R&D project grants is rather stable regarding the pool of beneficiaries. The question is whether this participation pattern can be justified by its realized effects. In addition, the impact of the grant size on the effects is investigated. Therefore, I allow to a certain extent for heterogeneous treatment effects in these two dimensions. Using a sample of about 8,500 observations, a non-parametric matching approach with multiple treatments is applied to estimate the effects of public R&D grants on firm's R&D input. The results show that particularly frequently given grants as well as medium and large grants are suitable to increase the scope of firm-financed R&D plans. For the analysis of the effects on firm's R&D output the R&D expenditures are disentangled in R&D which would have been spent in the absence of the grant and publicly induced R&D, including the grant and the effect on private R&D expenditures. Basically both types of R&D are equally productive in terms of innovative output. For the statement that a rather stable pattern of program participation leads to a lower effectiveness of the instrument no evidence has been found.
Keywords: C20; H32; O38; 330; R&D; Public Subsidies; Innovative Performance; Germany; Forschungssubvention; Industrielle Forschung; Wirtschaftspolitische Wirkungsanalyse; Forschungskosten; Innovation; Investition; Deutschland